Abakada Pampanga exploring instructional design methods integrated in the mother tongue-based multilingual education teaching methods in the Kapampangan language for children ages 5 to 7 in the kindergarten level of Floridablanca elementary school, Floridablanca, Pampanga - Dela Rosa, Ryan Carlo N.; Reyes, Mitzi Marie Aguilar (Quezon City College of Fine Arts, University of the Philippines Diliman, 2017)
The Mother Tongue-Based Multilingual Education (MTB-MLE) program of the Department of Education (DepEd) highlights the importance of using the mother tongue as the language of instruction in classrooms as mandated in all public schools across the Philippines. With this program, they aim to produce multilingual learners starting from the kindergarten basic level of education by strengthening their foundation in the mother tongue and as they further progress in the grade school level of the program, Filipino and English languages shall be introduced.

This study focuses on producing Kapampangan instructional materials for students ages 5-7 under the kindergarten curriculum of the Mother Tongue-Based Multilingual Education program of DepEd. To further advance the materials development phase of the program, students in the kindergarten section of the Floridablanca Elementary School was chosen as the polit school where this proposal will be situated on. The lack of instructional materials that reflect the kapampangan culture and language shows disconnection in the language teaching strategy of the MTB MLE to strengthen their foundation in their mother tongue. This calls for instructional design methods to be integrated in the current curriculum of the program.

Project abakada Pampanga aims to fill the lack of materials in the classroom of its target audience. Its goal is to further develop teaching and instructional materials that is developmentally appropriate and contextual to its users thus promoting culture as part of their language that can help the teachers and the students in language learning activities.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 145-148
Keywords: Mother Tongue-Based Multilingual Education (MTB-MLE); Abakada Pampanga; Teaching -- Aids and devices